Plant parasitic nematodes associated with ginger (Zingiber officinale) in Madhya Pradesh and denematization of infested rhizome by thermotherapy for management. - VADHERA, I; TIWARI, S P; DAVE, G S (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1991-94 on 9 genera of plant parasitic nematodes associated with ginger (Zingiberofficinale L.) in 6 districts of Madhya Pradesh. Meloidogylle incognita was predominant with 63% absolute frequencyof occurrence in the state. Denematization of ginger rhizomes by thermotherapy at 45Â°C for 3 hr disinfested the gingerrhizomes which resulted in the increased number of pseudo stems and shoot-root weight. When such disinfected gingerrhizomes planted in the field, there was 19.29-34.41 % 'increase in yield over control.